Kinase inhibitors for advanced medullary thyroid carcinoma (Clinics, 2012)
The recent availability of molecular targeted therapies leads to a reconsideration of the treatment strategy for patients with distant metastases from medullary thyroid carcinoma. In patients with progressive disease, treatment with kinase inhibitors should be offered.